Development and commercialization of pheromone-based biopesticides: a global perspective - Villarreal, Gabriela Unigarro [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; de Oliveira, Jhones Luiz [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2023)
Industrial agriculture relies on the utilization of great amounts of chemical pesticides for pre- and postharvest pest control. However, their effectiveness is limited and has resulted in pest resistance and environmental degradation, posing several challenges to agricultural ecosystems and soil health. Considering the global food demand for the year 2050, in the last few decades, global research has focused on developing innovative methods for protection against agricultural pests. One of the alternatives includes biopesticides, which are substances derived from biological sources for pest management in crop cultures. In addition, nanotechnology has offered new approaches in the form of nanobiopestcides, bringing the idea of minimal usage for maximum effect in the management of agricultural pests. This chapter underscores the utilization of pheromones in combination with nanotechnology as a safer alternative for pest control in modern agriculture practices, aiming to increase crop yield with minimal environmental impact.
Keywords: Agricultural science; Environmental protection; Environmental science; Nanobiotechnology; Nanotechnology; Pheromones; Sustainable development goals